Thrombus Burden of Deep Vein Thrombosis and Its Association with Thromboprophylaxis and D-Dimer Measurement: Insights from the APEX Trial - Chi, Gerald; Goldhaber, Samuel Z.; Hull, Russell D.; Hernandez, Adrian F.; Kerneis, Mathieu; Al Khalfan, Fahad; Cohen, Alexander T.; Harrington, Robert A.; Gibson, C. Michael (Thrombosis and Haemostasis, 2017)
Background The aim of this study was to evaluate the effect of betrixaban on the occurrence of deep vein thrombosis (DVT) and also the extent of thrombus and to assess the association of baseline D-dimer with subsequent thrombus burden.Methods In the APEX trial (ClinicalTrials.gov: NCT01583218), 7,513 acutely ill hospitalized medical patients were randomly assigned to extended-duration betrixaban (35–42 days) or enoxaparin (10 ± 4 days). D-dimer concentration was measured at baseline, and mandatory lower-extremity compression ultrasonography (CUS) was performed at 35 to 42 days. The thrombus burden of DVT was assessed by the number of non-compressible vascular segments in six target proximal veins and compared between treatment groups and D-dimer categories (≥2 × upper limit of normal [ULN] versus <2 × ULN).Results Compared with enoxaparin, extended-duration betrixaban reduced the DVT risk at 35 to 42 days (any-dose: relative risk [RR] = 0.76 [95% confidence interval: 0.61–0.94]; p = 0.013; full-dose: RR = 0.70 [0.55–0.90]; p = 0.005). Patients who received betrixaban were more likely to have a lower thrombus burden (p = 0.012 for any-dose and p = 0.001 for full-dose). Elevated D-dimer at baseline was independently associated with a 2.12-fold increased risk of developing DVT (p < 0.001). A greater thrombus burden was also observed in those with D-dimer ≥ 2 × ULN compared with <2 × ULN (p < 0.0001).Conclusion Extended-duration betrixaban reduced the number of venous segments with thrombosis at 35 to 42 days compared with enoxaparin. A positive D-dimer was associated with a greater extent of thrombus burden among acutely ill medical patients who developed DVT despite receiving thromboprophylaxis.Clinical Trial Registration: URL: http://www.clinicaltrials.gov. ClinicalTrials.gov identifier: NCT01583218.
Keywords: venous thrombosis; venous thromboembolism; D-dimer; anticoagulants; factor Xa inhibitors